Training to Strengthen Competency of School Principals in the Implementation of the Independent Curriculum - Nurdin, Diding; Suryadi, Suryadi; Uum Murfiah; Arip Amin (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
The training on strengthening school leadership competencies in the implementation of the Independent Curriculum is a community service program aimed at supporting school principals in addressing new challenges in the field of education. The Independent Curriculum emphasizes more flexible learning and focuses on developing the individual potential of students, requiring adaptive and innovative leadership from school principals. The service method used includes workshops, group discussions, and case studies involving the active participation of school principals from various educational levels. The results of the training show an improvement in principals' abilities to manage change, effectively implement the Independent Curriculum, and enhance the quality of learning in their respective schools. In conclusion, strengthening school leadership competencies in the implementation of the Independent Curriculum is an essential step to support the achievement of high-quality education that is relevant to current developments. Keywords: competence, leadership,principalship, Merdeka curriculum Abstrak Pelatihan penguatan kompetensi kepemimpinan kepala sekolah dalam implementasi Kurikulum Merdeka merupakan program pengabdian masyarakat yang bertujuan untuk mendukung kepala sekolah dalam menghadapi tantangan baru dalam dunia pendidikan. Kurikulum Merdeka menekankan pada pembelajaran yang lebih fleksibel dan berfokus pada pengembangan potensi peserta didik, sehingga membutuhkan kepemimpinan yang adaptif dan inovatif dari kepala sekolah. Metode pengabdian yang digunakan adalah pelatihan berbasis workshop, diskusi kelompok, dan studi kasus yang melibatkan partisipasi aktif kepala sekolah dari berbagai jenjang pendidikan. Hasil pelatihan menunjukkan peningkatan kemampuan kepala sekolah dalam mengelola perubahan, menerapkan Kurikulum Merdeka secara efektif, serta meningkatkan kualitas pembelajaran di sekolah masing-masing. Simpulan bahwa penguatan kompetensi kepemimpinan kepala sekolah dalam implementasi Kurikulum Merdeka merupakan langkah penting untuk mendukung tercapainya pendidikan yang berkualitas dan relevan dengan perkembangan zaman. Kata kunci: